Pacidius Philalethi: contrapunto de maduración - Kasahara Barrientos, Javier (2014)
This paper proposes a second lecture of the text Pacidius Philalethi of G. W. Leibniz in which two aspects stand out: first, the consideration of the importance that the problem of the continuum poses in Leibniz’s metaphysics and, second, the search for an understanding of the main genetic character in the maturity of Leibniz’s thought.